2016
DOI: 10.14198/jhse.2016.111.03
|View full text |Cite
|
Sign up to set email alerts
|

Age of peak performance in Olympic sports: A comparative research among disciplines

Abstract: Longo, A.F., Siffredi, C.R., Cardey, M.L., Aquilino, G.D., & Lentini, N.A. (2016). Age of peak performance in Olympic sports: A comparative research among disciplines. J. Hum. Sport Exerc., 11(1),[31][32][33][34][35][36][37][38][39][40][41]. This research aimed to study the ages of peak performance in Olympic sport disciplines, and to distinguish age groups among them. The ages (in decimal years) of athletes with the best performances at the 2012 Summer Olympics were considered (n = 3548). A total of forty spo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 9 publications
0
38
0
1
Order By: Relevance
“…In general, it is observed that endurance sports athletes, such as those competing in track and field [ 9 ], middle and long-distance running [ 10 ], and ski marathon [ 11 ], seemed to reach their peak performance in older ages when compared to athletes from sports disciplines requiring explosive power and speed [ 3 ]. In addition, some sex differences in the age of peak performance in runners have also been pointed out.…”
Section: Introductionmentioning
confidence: 99%
“…In general, it is observed that endurance sports athletes, such as those competing in track and field [ 9 ], middle and long-distance running [ 10 ], and ski marathon [ 11 ], seemed to reach their peak performance in older ages when compared to athletes from sports disciplines requiring explosive power and speed [ 3 ]. In addition, some sex differences in the age of peak performance in runners have also been pointed out.…”
Section: Introductionmentioning
confidence: 99%
“…This process could subsequently lead to better performances, satisfaction, higher motivation, and increased enjoyment, 4,5 all of which contribute to persistence in sports activity. 6 Although early diversification is suggested, especially in late specialization sports such as cycling, 7,8 this does not alter the fact that young athletes may already prepare themselves in the discipline that suits him/her the most.…”
Section: Introductionmentioning
confidence: 99%
“…Tabel 1 adalah lampiran hasil pengukuran awal. Berdasarkan hasil pada Tabel 1 dapat disimpulkan bahwa nilai rata-rata usia sampel dari kedua kelompok pada saat pengambilan data semuanya berada dalam kelompok usia produktif yaitu pada usia ±18.3 tahun (Longo et al, 2016), dan nilai Indeks Massa Tubuh sampel pada kedua kelompok juga terlihat dalam keadaan normal 21.12kg/m2 pada kelompok eksperimen dan 21.78kg/m2 pada kelompok kontrol (Markowitz, 2018). Mayoritas sampel di kedua kelompok juga memiliki angka kecukupan protein yang baik dengan kisaran 68-69 gr/hari (Close et al, 2016).…”
Section: Analisa Deskriptifunclassified